Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1364/ol.41.003201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad supercontinuum generated from a highly nonlinear Ge–Sb–Se fiber

Abstract: We report the fabrication of a novel high nonlinear fiber made of Ge-Sb-Se chalcogenide glasses with high numerical aperture (∼1.0), where the core and the cladding glasses consist of Ge15Sb25Se60 and Ge15Sb20Se65 (mol. %), respectively. The nonlinear refractive index (n2) of the core glass is 19×10-18 m2/W at 1.55 μm, and its laser-induced damage threshold under irradiation of 3.0 μm fs laser is approximately 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…In order to produce ultrabroadband SC sources with high brightness that can cover the spectral evolution up to the molecular fingerprint region, researchers have proposed the use of optical waveguides made with different host materials such as fluoride, tellurite and chalcogenide glasses [5,6,7,8,9,10,11,12,13]. The MIR transparencies of fluoride and tellurite glasses are not more than 5 µm [14] and until to date the highest SC extension in the long wavelength edge by these two materials are 6.28 µm [15] and 4.87 µm [16], respectively. At the same time, chalcogenide (ChG) glasses have shown wider MIR transparency exceeding 20 µm, depending on the compositions of glass components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to produce ultrabroadband SC sources with high brightness that can cover the spectral evolution up to the molecular fingerprint region, researchers have proposed the use of optical waveguides made with different host materials such as fluoride, tellurite and chalcogenide glasses [5,6,7,8,9,10,11,12,13]. The MIR transparencies of fluoride and tellurite glasses are not more than 5 µm [14] and until to date the highest SC extension in the long wavelength edge by these two materials are 6.28 µm [15] and 4.87 µm [16], respectively. At the same time, chalcogenide (ChG) glasses have shown wider MIR transparency exceeding 20 µm, depending on the compositions of glass components.…”
Section: Introductionmentioning
confidence: 99%
“…A number of numerical and experimental ultrabroadband SC spectra in the MIR region using ChG waveguides and fibers have been demonstrated quite recently [4,10,11,12,13,14,31,32,33]. Yu et al [12] demonstrated a SC spectrum covering a wavelength range from 1.8 to 10 µm with a pulse duration of 330-fs pumped at 4 µm in a 11-cm long ChG step-index fiber using Ge 12 As 24 Se 64 as a core and Ge 12 As 24 S 64 for its outer cladding with an input peak power of 3 kW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic and antimony are known to increase glass formation region [11] as well as refractive and nonlinear indices [12,13]. Indeed, most of SC spectra reported in chalcogenide glass (ChG) fibers are obtained with sulfide, selenide or telluride based compositions containing arsenic and/or antimony such as As2S3 [14], As2Se3 [15,16], GeAsS,GeAsSe [17,18], GeAsSeTe [19,20], GeSbS(Ga), GeSbSe [17]. To the best of our knowledge, only one study reports SC obtained with a ChG fiber free of arsenic and antimony [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the Antimony (Sb) assists the shifting of the multi-phonon edge to longer wavelengths. In addition, it has relatively large nNL and high laser damage threshold of about 3674 GW/cm 2 which is more than twice times larger compared to As2Se3 glass [14][15][16].…”
Section: Introductionmentioning
confidence: 99%